Parenting Management Strategies for the Cultivation of Disciplined Character at the Police Academy - Sigit Susilo; Arief Yulianto; Tri Joko Raharjo (The Journal of Educational Development, 2025)
In today's global era, the demand for professionalism and discipline in law enforcement is increasing, so the Police Academy plays a vital role in instilling kebhayangkaraan values to form cadets who can face security challenges with discipline, integrity, ethics, and strong leadership. This study profoundly analyses how the parenting management model instils the main kebhayangkaraan character in the discipline character. The research method used is qualitative with a phenomenological approach, where data are obtained through in-depth interviews, participatory observation, and documentation. The results showed that parenting with a structured schedule and consistent enforcement of rules succeeded in instilling discipline in cadets. Intensive physical exercise, discipline classes, and character-building sessions significantly improve cadets' discipline and mental endurance. Periodic evaluations and feedback from cadets help improve parenting programs continuously. In conclusion, holistic and integrated parenting management effectively instils disciplinary character in Level I Cadets of the Police Academy.